Functional Analysis in Cognitive Behavioral Solution Focused Brief Therapy - Cade Blake (Global Writing Academica Researching and Publishing, 2023)
Recently it has been published evidence of the successful implementation of the integration of solution focused brief therapy and behavioral cognitive therapy as a model of brief therapy that is currently used as the basis for the Master of Brief Therapy in the Autonomous University of Nuevo Leon. However, in the application some process have showed some issues that could be systematized, some of them include the use of functional analysis as a basis for the design of treatment and to specify the minimum elements to consider that the therapeutic model used corresponds to the integration of the two approaches. Thus, the aim of this paper is to systematize the practice model integrating behavioral cognitive therapy and solution-focused therapy and to propose a guide to the practical integration of these approaches based on functional analysis.